Mobile Assisted Language Learning (MALL) to Enhance Students Speaking - Fera Pratiwi, Dian; Julianti, Rahmah; Dewi Anggung, Sinta; Ima, Nur; Mutmainnah Halim, Nur (Hasanuddin University, 2024)
This research concerned and focused on the effect of the implementation of MALL on the students' speaking achievement and find out whether or not the students are interested in learning English speaking comprehension through SpeakingPal Application as a part of Mobile Assisted Language Learning (MALL). This research employed a quasi-experimental research method. The instrument of this research involved a speaking test, questionnaire, and interview. This research used a purposive sampling technique. The respondents of this research were from two different classes and each class was assigned to two different groups which were Experimental and Control groups. Each group consists of 25 students. The Experimental group was the group that was given the treatment by using Mobile Assisted Language Learning (MALL) while the control group was given the Conventional teaching and learning method. The effectiveness of the treatment was determined by comparing the post-test scores of both groups. The data regarding students' speaking achievement was collected by speaking tests, questionnaires, and interviews were used to collect the data regarding with the student's interest. The result of this study showed that there was a significant difference between the students’ scores taught by using SpeakingPal and the conventional method. It was proven by the mean score of the experimental group After the treatment applied the difference scores of the posttest between experimental and control group were huge. It means that there was an impressive improvement after treatment applied for experimental group. The mean score of the students‟ pretest of experimental group was 10.20 with standard deviation 1.53; meanwhile the mean score of the students‟ pretest of control group was 8.20 with standard deviation 1.66. And the mean score of the students‟ posttest of experimental group was 14.12 with standard deviation 2.33; while the mean score of students‟ posttest of control group was 10.36 with standard deviation 1.73. It means that the mean score of posttests from both groups were higher than pretest (10.20<14.12) and (8.20<10.36). The test result indicated that the implementation of SpeakingPal had a significant effect in improving students' speaking achievement. From the questionnaire and interview the data showed that 64% of students were categorized as highly interested and 32% of students were categorized as interested level. So, it can conclude that the implementation of SpeakingPal positively affected the students’ speaking achievement and the students were highly interested in learning to speak by using the SpeakingPal application.